2021
DOI: 10.1111/eci.13531
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐regional pro‐atrial natriuretic peptide independently predicts short‐term mortality in COVID‐19

Abstract: Background: Mid-regional pro-atrial natriuretic peptide (MR-proANP) is a strong prognostic marker in several inflammatory, respiratory and cardiovascular conditions, but has not been studied in COVID-19 yet. Methods: This prospective, observational study of patients with COVID-19 infection was conducted from 6 June to 26 November 2020 in different wards of a tertiary hospital. MR-proANP, N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitive cardiac troponin I levels on admission were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We have previously published data from the same study population and reported on the prognostic impact of Mid-regional pro-atrial natriuretic peptide among other biomarkers (creatinine, blood urea nitrogen, LDH, hs-cTnI, NT-proBNP) on 28-day mortality [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously published data from the same study population and reported on the prognostic impact of Mid-regional pro-atrial natriuretic peptide among other biomarkers (creatinine, blood urea nitrogen, LDH, hs-cTnI, NT-proBNP) on 28-day mortality [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our population 43 subjects were obese (63.2%), 12 subjects were affected by diabetes mellitus (17.6%) and 45 subjects were affected by arterial hypertension (66.2%). The median length of stay (LOS) in ICU was 13 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] days, while the median LOS in hospital was 20 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] days. Demographic, clinical and biochemical characteristics of the enrolled patients are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The attempt to find a possible correlation between some endocrinological markers and COVID-19 severity has already been investigated in the literature with encouraging results [11][12][13][14][15]. For sure, in light of the longer half-life and stability of mid-regional pro-adrenomedullin (MR-proADM), copeptin and mid-regional pro-atrial natriuretic peptide (MR-proANP), with respect to their biologically active counterpart (namely ADM, AVP-arginine vasopressin-and ANP), the research focus has been shifted especially to these three markers.…”
Section: Introductionmentioning
confidence: 99%
“…There are several pathophysiological links that may contribute to the association of MR-proANP with COVID-19. Most of these mechanisms are closely linked to pathophysiological considerations with NT-proBNP, since both biomarkers are secreted upon volume overload, one primarily by ventricular and the other by atrial myocytes [85].…”
Section: Mr-proanpmentioning
confidence: 99%